STRATEGI, PERAN DAN FUNGSI KEHUMASAN DI LEMBAGA PENDIDIKAN ISLAM - Viktori Aziz; Rohmat (CV. Amerta Media, 2022)
One of the important aspects of educational institutions is managing public relations (PR), because educational institutions are in the midst of society and are always in touch in establishing pedagogical and sociological cooperation so that it benefits both parties. Likewise with Islamic Educational Institutions (pesantren) which inevitably have to start shifting from their previous understanding by paying attention to the public relations strategy with all its requirements. One of the strategies to introduce the institution is to create and introduce a central icon (the figure of the kyai) which must be packaged in such a way that in addition to the kyai having qualified religious abilities, the kyai figure is also required to have high integrity. In addition to the competence and integrity of the kyai, Islamic educational institutions must also begin to develop a more professional institutional management system. Keywords: strategy, role, function of public relations, Islamic educational institutions